Monitoring chemical changes of binding carbohydrates and simulation of temperature profiles during sterilization of oil palm fruit bunches - Thang, Yin Mee (2021)
In a typical palm oil milling process, 30 tons to 60 tons of fresh fruit bunches are processed together and this may cause difficulties for heat to penetrate especially to those fruitlets located at the centre of a large and compact bunch. A complete detachment of the fruitlets is possible only if the moist heat can reach the abscission zone of the fruits to the stalk. A greater understanding of the fundamentals of fruit detachment is necessary as it is shown that the strippability of the sterilized fruitlets would ultimately affect the oil extraction rate. The study began with the characterization of the binding carbohydrates at the abscission zone of fruitlets before and after sterilization. Response surface methodology (RSM) was applied to model the sugar compositions in sterilized fruits by varying the parameters of pressures, sterilization time, and ripeness of FFBs. Finally, a heat transfer modelling using sophisticated gPROMS software was conducted to provide insights into the heat transfer mechanism inside the sterilizer and FFBs. The FFBs were collected according to the number of empty fruit sockets: (i) nil; (ii) 1-9; (iii) ≥10 as unripe, under-ripe, and ripe bunches, respectively. The PCA plots revealed that the oligomers are the chemical markers that are responsible for differentiating the ripe samples from the others. Both non-structural and structural sugars are the factors that differentiate under-ripe samples from the rest. All experiments showed some level of the detachment of sterilized fruits after the sterilization. Low sterilization pressure or short holding time resulted in insufficient cell wall rupture, thus a high percentage of unstripped bunches. HPLC analysis showed that large percentages of oligomers were observed in sterilized fruits, ranging from 2.05- 11.44 w/v%. Only about 0.15-1.19 w/v% of simple sugars were detected in sterilized fruits. RSM optimization confirmed that oligomers could be used as a biomarker to relate to fruits strippability after sterilization. In addition, gPROMS has successfully predicted the temperature profiles in the sterilization experiments. The simulation proposed that the sterilized fruits could only be 100% stripped if the temperature of FFBs is kept above 48oC for at least 53.5 mins. In addition, the oligomers content of sterilized fruits must be more than 3.8 w/v%. Under this optimum condition, the rate of oil loss will be lower and the OER will ultimately be improved.